Media Interaktif Pemahaman Konsep Bangun Ruang pada Pembelajaran Matematika dengan Media Interaktif di SDN 12 Padang Besi - Tasha Wulandari Liandri; Adrias Adrias; Salmaini Safitri Syam (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Understanding geometric concepts is an essential part of the mathematics learning process in elementary school. However, many fifth-grade students face challenges in grasping these concepts due to monotonous and less interactive learning media. These difficulties contribute to students' low comprehension of geometric concepts. The purpose of this study is to analyze the contribution of interactive media in strengthening students' understanding of geometric concepts in elementary school. The research employs a qualitative approach, with data collected through observations, interviews with teachers and students, and documentation. The findings reveal that less interactive teaching methods, the lack of concrete learning media, and an unconducive learning environment are the main factors hindering students' understanding. Increasing student participation and facilitating their comprehension of geometric concepts can be achieved by implementing interactive media such as digital simulations, animated videos, and educational games. Thus, interactive media can enhance students' learning motivation and create a more enjoyable learning atmosphere. By integrating interactive media into the mathematics learning process, students are expected to become more actively engaged, focused, and able to understand geometric concepts more effectively.